Partisipasi Masyarakat dalam Mitigasi Bencana Banjir di Kecamatan Pulau Laut Utara Kabupaten Kotabaru - Dwi Sintia; Ghinia Anastasia Muhtar (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the forms of community participation in flood disaster mitigation in Pulau Laut Utara District and the types of mitigation efforts undertaken in Pulau Laut Utara District. This study used a quantitative descriptive research method. Data collection techniques included observation, questionnaires, and documentation. Data analysis used a Likert scale.The results indicate that community participation in flood disaster mitigation in Pulau Laut Utara District has developed in terms of physical and social involvement, but has not been accompanied by an increase in the community's intellectual and technical capacity. This situation indicates that the implemented disaster mitigation approach still needs to be directed at more comprehensive community empowerment, so that the community plays a role not only as an implementer of activities but also as a planner, decision-maker, and agent of change in disaster risk reduction. The results of the study indicate that the level of disaster mitigation in Pulau Laut Utara District is generally in the high category. These results indicate that efforts to reduce the risk of flood disasters have been implemented through the application of complementary structural and non-structural mitigation.